China, Brasil e Piauí:nova regionalização no “cerrado piauiense” em face da dinâmica da geopolítica contemporânea (2008 – 2019) - Raimundo Jucier Sousa de Assis (Confins)
This article analyzes the commercials trade between Brazil and China. This trade was intensified after the 2008 economic crisis, emphasizing their impact in the southwest of the federated state of Piauí, in the northeast of Brazil. To perform this analysis, we interpret three bilateral agreements, signed between these two countries: bilateral action plan Brazil-China (2010-2014); Ten-years cooperation plan (2012-2020) and the second bilateral action plan Brazil-China (2015-2021). Next, the data of export and import were analyzed on the statistical basis, highlighting the results in the southeast of Piauí (2008-2019). The databases were collected from the platform of the Ministry of Economy. Among the results, it is possible to highlight the six municipalities in the state of Piaui that form a new regionalization. This new circuit is organized by the penetration of the Chinese economy in the territory of Brazil and it arises from alliances between states and economic exchanges after the 2008 crisis.